PERSPEKTIF WACANA DAN ANALISISNYA - Agus Supriatna (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2016)
This paper entitled "Discourse Perspective and Analysis" a critique to the development of discourse and its theoretical analysis. The method used is descriptive analytic with discourse analysis approach. The term of discourse has been very popular in Indonesia nowadays, especially those related to political discourse. But not a few people even understand the word of discourse to something that is not necessarily true. If seeing the meaning of true discourse, it is more positive word based on the viewpoint of the scientific language of discourse. Discussion of the results obtained that the discourse and analysis can be viewed from various angles. In the world of science in this case there are two linguistic perspective in view of discourse that is structuralism and post structuralism. Keywords: perspective, analysis, discourse